The influence of principal leadership and compensation on teacher’s performance at state junior high school - Renawati Renawati; Yasir Arafat; Mulyadi Mulyadi (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aimed to determine: (1) the influence of principal leadership on teachers’ performance; (2) the influenceof compensation on teachers’ performance; and (3) the influenceof principal leadership and compensation simultaneously on teachers’ performance. The data in this study were collected through distributing questionnaires to respondents and were analyzedby using multiple regression analysis through the t test, F test, and determination coefficient test. The population in this study were all teachers of SMP NegeriatBabatSupat sub-district, MusiBanyuasin Regency, totaling 134 people. The sampling technique used was probability sampling by using the Slovin formula to obtain 100 teachers as the research sample. The results of the study found that: (1) there was a significant influence between principal leadership on teachers’ performance; (2) there was a significant influence between compensation on teachers’ performance; (3) there was a significant influence between principal leadership and compensation on teachers performance.